Effects of Gemfibrozil on Lipids and Haemostasis after Myocardial Infarction - Andersen, P; Smith, P; Seljeflot, I; Brataker, S; Arnesen, H (Thrombosis and Haemostasis, 1990)
The effects of gemfibrozil on haemostatic variables were studied in 43 survivors of myocardial infarction with serum triglycerides (TG) ≥2 mmol/1 2 weeks prior to randomization. The study was double-blind, placebo-controlled and stratified for chronic betablockade. Twenty-two individuals were given gemfibrozil 600 mg twice daily and 21 individuals received matching placebo. After 8 weeks the TG level was unchanged in the placebo group, whereas a 44% reduction was noted in the gemfibrozil group (p <0.0001). Fibrinogen increased in both groups, while bleeding time and platelet count were unchanged. Clotting factor VH-phospholipid complex decreased in both groups, but the change was more marked and attained statistical significance only in the gemfibrozil group (60% reduction, p <0.01). By DDAVP-stimulated D-Dimer agglutination test 8 in 21 patients in the placebo group (38%) still had reduced fibrinolytic capacity versus none in the gemfibrozil group (p = 0.001). Thus, in this study, gemfibrozil improved reduced fibrinolytic capacity and may have reduced hypercoagulability by lowering the clotting factor VH-phospholipid complex.